PENDIDIKAN ISLAM DAN BAHASA ARAB MULTIKULTURAL DI MADRASAH - Ahmad Rifa'i (IAIN Kediri, 2015)
Multicultural education means to learn about, prepare for, and celebrate cultural diversity. It requires changesÂ in school programs, policies and practices. Experts agreed that the content, structure and specific practices inÂ multicultural education are different according to the settings. This article will focus its discussion on multuralÂ education in teaching Arabic language. It found that multicultural education in teaching and learning ArabicÂ language can be implemented in maá¸¥Ärah al-arbÄâ€™, including learning maá¸¥Ärah qirÄâ€™ah, mahÄrah kalÄm,Â mahÄrah kitÄbah, and mahÄrah istimÄâ€™. In globalization era, problems of multiculturalism are inevitable,Â including in learning Arabic because language is a human culture, which has different characteristics in termsÂ of race, ethnicity, religion, geography and language.Keywords: Pendidikan Multikultural, Bahasa Arab, Maá¸¥Ärah al-ArbÄâ€™